Visible light communication for advanced driver assistant systems - Kumar, Navin (2012)
VIsible light communication for advanced Driver Assistant Systems (VIDAS) is an outdoor application using the visible spectrum of light emitting diodes (LED). A simple traffic light set up based on LED traffic lights for traffic information transmission has been analyzed in this paper. Various important design parameters have been optimized through intensive investigation based on gain variation over 100 m of transmission range. This process is expected to simplify the front-end receiver design and enhance the performance of the receiver which is one of the most critical elements in a visible light communication (VLC) transceiver, especially in outdoor applications. Our design results show receiver adaptability for different packet sizes and different distances.